PRINCIPLES, NORMS AND STRATEGIES OF THE US GLOBAL CYBERSPACE GOVERNANCE - Nageen Ashraf; Muhammad Nadeem Mirza (Margalla Papers, 2025)
This study examines the United States' (US) approach to global cyber governance, including the principles, strategies, and norms the US intends to promote in cyberspace. This also discusses why the US is unwilling to share cyberspace governance with other great powers. These are the questions this study intends to answer. While utilizing the official policies and strategies of the US as primary sources, this study identifies that the core principles of US cyber governance encompass a free and open internet, a multi-stakeholder approach, collaboration with allies, and maintaining a stable and secure digital landscape. However, it is criticised for its approach to data privacy, the Internet Corporation for Assigned Names and Numbers (ICANN) control, mass surveillance programs against foes and allies, and its disagreement with other states on cyberspace governance.